Reports of Judgments, Advisory Opinions and Orders 2021: Alleged Violations of the 1955 Treaty of Amity, Economic Relations, and Consular Rights (Islamic Republic of Iran v. United States of America) - International Court of Justice (United Nations, 2022)
Judgment on the preliminary objections raised by the United States.